An evaluation of overseas oil investment projects under uncertainty using a real options based simulation model - Lei Zhu; ZhongXiang Zhang; Ying Fan (Fondazione Eni Enrico Mattei (FEEM), 2011)
This paper applies real options theory to establish an overseas oil investment evaluation model that is based on Monte Carlo simulation and is solved by the Least Squares Monte-Carlo method. To better reflect the reality of overseas oil investment, our model has incorporated not only the uncertainties of oil price and investment cost but also the uncertainties of exchange rate and investment environment. These unique features have enabled our model to be best equipped to evaluate the value of oil overseas investment projects of three oil field sizes (large, medium, small) and under different resource tax systems (royalty tax and production sharing contracts). In our empirical setting, we have selected China as an investor country and Indonesia as an investee country as a case study. Our results show that the investment risks and project values of small sized oil fields are more sensitive to changes in the uncertainty factors than the large and medium sized oil fields. Furthermore, among the uncertainty factors considered in the model, the investment risk of overseas oil investment may be underestimated if no consideration is given of the impacts of exchange rate and investment environment. Finally, as there is an important trade-off between oil resource investee country and overseas oil investor, in medium and small sized oil investment negotiation the oil company should try to increase the cost oil limit in production sharing contract and avoid the term of a windfall profits tax to reduce the investment risk of overseas oil fields.
Keywords: Q41; Q43; Q48; G31; O13; O22; C63; 330; Overseas Oil Investment; Project Value; Real Options; Least Squares Monte-Carlo